2011
DOI: 10.1002/em.20673
|View full text |Cite
|
Sign up to set email alerts
|

Differences in the frequencies of K‐ras c12–13 genotypes by gender and pathologic phenotypes in colorectal tumors measured using the allele discrimination method

Abstract: The frequencies of different genotypes of the K-ras oncogene in colorectal cancer (CRC) reveal complex relationships among gender, age, and tumor aggression, however, differences among these studies could also be attributed to a lack of standardization of the detection methods used. We developed the allele discrimination assay, which uses dual-color real-time polymerase chain reaction (qPCR) as a fast K-ras genotyping method, and demonstrated higher sensitivity and specificity than DNA sequencing with formalin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 31 publications
0
7
0
Order By: Relevance
“…39 This complies with observations of higher KRAS mutation frequencies in CRC from female than in male patients. 13,43 Some studies, however, find the higher KRAS frequency in females only relevant in younger individuals or limited to CRC located in the distal colon or rectum. 39,[44][45][46] These factors are consistent with our data as both young age in terms of CRC risk and dominance of distally located polyps are present.…”
Section: Discussionmentioning
confidence: 99%
“…39 This complies with observations of higher KRAS mutation frequencies in CRC from female than in male patients. 13,43 Some studies, however, find the higher KRAS frequency in females only relevant in younger individuals or limited to CRC located in the distal colon or rectum. 39,[44][45][46] These factors are consistent with our data as both young age in terms of CRC risk and dominance of distally located polyps are present.…”
Section: Discussionmentioning
confidence: 99%
“…This recommendation is supported by 15 studies, [128][129][130][131][132][133][134][135][136][137][138][139][140][141][142] comprising eight prospective cohort studies [130][131][132][133][136][137][138]142 and seven retrospective cohort studies. 128,129,134,135,[139][140][141] For the eight prospective cohort studies, [130][131][132][133][136][137][138]142 all reported balance between the treatment and assessment groups, as all but one 132 used a single cohort design allowing for within-group comparisons. Only this single study, reported by Tol et al, 132 would have required making adjustments for imbalances between the treatment and assessment groups, but none were needed.…”
Section: Postanalytical Variablesmentioning
confidence: 99%
“…Only this single study, reported by Tol et al, 132 would have required making adjustments for imbalances between the treatment and assessment groups, but none were needed. Five studies 130,133,[136][137][138] reported nonindustry funding, one 132 reported at least partial industry funding, one 142 reported industry funding, and one 131 did not disclose the source of funding, if any. Seven 130,131,133,[136][137][138]142 were deemed to have a low risk of bias, and one 132 was deemed to have a low to moderate risk of bias.…”
Section: Postanalytical Variablesmentioning
confidence: 99%
See 2 more Smart Citations